Soldagem MIG/MAG com fluxo ativo do aço inoxidável austenítico AISI 304L - Luana Araújo Batista (2018)
MIG/MAG welding is one of the most commonly used metal joining processes, being characterized by high productivity and ease of automation. A new variant of the MIG/MAG process that uses active fluxes, called A-MIG in a dissertation, presents potential to modify the operational characteristics of the weld and the profile of the weld bead. A-MIG welding basically requires the same resources used in conventional MIG/MAG process except for the application of a thin layer of flux over the region to be welded. In order to verify the influence of different fluxes on the operational characteristics of A-MIG welding of an austenitic stainless steel, initial welding trials with six different flux candidates were performed with short-circuit metal transfer. Two fluxes that presented stronger capacity to affect welding conditions were selected from these trials and evaluated in free flight metal transfer trials with constant current operation. The results show that most of the used fluxes can present active behavior in MIG welding of stainless steels, causing changes in process electrical characteristics and weld bead shape. Some of the effects caused by these fluxes were changes in arc voltage and current, the metal transfer frequency and higher arc luminosity. Among the tested flux candidates, silica and calcium carbonate were those that more strongly affected the welding conditions